KAJIAN RANCANGAN UNDANG-UNDANG PEMBERANTASAN TINDAK PIDANA TERORISME - Wulandari, Ria (TANJUNGPURA LAW JOURNAL, 2017)
At this time, Indonesian revising for the anti terrorism number 15 year 2003. It’s cause pro and contra about the draft of articles. The issue that often turn up is the anti terrorism article drafts should more against terrorism crime and all at once human right respectful.This article study about interpretation of article drafts and comparison with the anti terrorism number 15 year 2003. So, the more and less of article drafts will be knowing. Revise for the anti terrorism number 15 year 2003 hoping can find strategic and tactis to overcome terrorism crime without shake Indonesian social and culture system.